Effect of Presprouting of Seeds on Field Duration of Short and Long Duration Potato Varieties in Haor Ecosystem - Karim, MM; Bhuiya, MSU; Das, BC; Hossain, SMA (Journal of Environmental Science and Natural Resources, 2013)
A field experiment was conducted at the farmers field of Livelihood Improvement of Farming Community in Haor Area through System Approach Project site Purbo Tethulia, Mohangonj, Netrakona during the Rabi Season of 2011-2012 to shorten the field duration of potato through seed pre-sprouting technique and to find out the suitable potato variety for cultivation in Dingaputa haor area without affecting the cultivation period of boro rice. Diamont and one local variety Challisha were taken for the study. Pre-sprouting duration of Diamont was 10, 20, 30 and 40 days with un-sprouted Diamont and Challisha. In the study unsprouted Diamont produced significantly the highest yield (25.28 tha-1) followed by 20.01, 13.46, 13.31, 12.74 and 11.54 tha-1 of 10, 20, 30, 40 days pre-spouted Diamont and un-sprouted Challisha, respectively. The lowest field duration of the crop was 41 days of 30 and 40 days pre-spouted Diamont. The highest gross margin of Tk.165960 ha-1 was observed from the unsprouted Diamont potato against the variable cost of Tk.137400 ha-1 incurred. The performance of Challisha was also appreciated by the farmers for its quality and low cost of production. Unsprouted Diamont potato also ranked the top most position in terms of benefit cost ratio of 2.21. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14815 J. Environ. Sci. & Natural Resources, 5(2): 205-207 2012